Impacts of Shrub Encroachment on Vegetation Community and Soil Characteristics in Coastal Wetlands of the Abandoned Yellow River Course - Jiaxuan Liu; Mengjiao Luo; Fanzhu Qu; Bowen Sun; Yang Yu; Ling Meng (Agronomy)
Shrub encroachment in coastal wetlands alters vegetation–soil interactions, yet its impacts on north temperate coastal wetland ecosystems remain poorly quantified. This study investigated the effects of Tamarix chinensis-dominated shrub encroachment in the abandoned Yellow River course wetlands. Encroachment stages (Isolated Tamarix shrub, ITS → Tamarix shrub island, TSI → Tamarix woodland, TWL) were assessed via vegetation surveys and soil sampling (0–60 cm). Encroachment progression significantly increased shrub cover, shrub crown width, and branches per shrub while reducing soil electrical conductivity and soil salt content. Surface soils (0–5 cm) exhibited higher levels of organic carbon (SOC) and elevated total nitrogen (TN) and available nitrogen (AN), while deeper layers (40–60 cm) at the TWL stage exhibited reduced available phosphorus (AP) and total phosphorus (TP). Redundancy analysis (RDA) identified soil bulk density, soil water content, total carbon (TC), and AP as primary drivers of vegetation community restructuring (RDA: 68.68% variance). The average ranges of TC:TN (RCN), TC:TP (RCP), and TN:TP (RNP) were 23.04–92.54, 52.14–92.88, and 0.46–4.29, respectively. T. chinensis encroachment induced nitrogen-limited conditions and reduced deep soil layer phosphorus availability, fundamentally restructuring coastal wetland ecosystems. These findings inform blue carbon ecosystem management in the north temperate zone.